Intubation in a Patient with Ice-Pick in the Spine: Molar Approach of Direct Laryngoscopy to our Rescue - Bala, Renu; Singh, Raj; Dhankar, Sheetal; Beniwal, Rajeev (Indian Journal of Neurotrauma, 2016)
Intubation in patients with spine injury is difficult due to several reasons. In patients with retained foreign body in the spine, difficulty is aggravated by imperfect position and risk of neurologic deterioration. We overcome this difficulty with a simple alternative method of intubation.
Keywords: ice-pick; spine injury; airway management; intubation